DEVELOPING CREATIVE COMPETENCE THROUGH AN INTEGRATIVE PEDAGOGICAL MODEL AND ITS FOUNDATIONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study examines the pedagogical foundations of developing pre-service teachers’ creative competence through an integrative approach. The research analyzes the historical evolution of the concept of competence, the structural components of pedagogical competence, as well as the content and key indicators of creative competence based on scientific sources. A methodological model grounded in an integrative approach is proposed, in which motivational, cognitive, practical, and reflective components are justified step by step. Furthermore, methodological principles underpinning the model such as integration, gradual development, reflection, creative tasks, and active learner participation are defined and theoretically substantiated.